Homogenization of soil seed bank communities by fire and invasive species in the Mojave Desert - Lee, Steven; Klinger, Robert; Brooks, Matthew L.; Ferrenberg, Scott (Frontiers in Ecology and Evolution, 2024)
Soil seed banks help maintain species diversity through temporal storage effects and function as germination pools that can optimize fitness across varying environmental conditions. These characteristics promote the persistence of native plant communities, yet disturbances such as fire and associated invasions by non-native species can disrupt these reserves, fundamentally altering successional trajectories. This may be particularly true in deserts, where native plant communities are less adapted to fire. While studies of fire effects on desert plant communities are not uncommon, information regarding the short-and long-term effects of fire on seed banks is less available. To better understand the influence of fire and invasive species on desert seed banks, we investigated soil seed bank biodiversity from 30 wildfires that burned between 1972 and 2010 across the Mojave Desert ecoregion of North America. We assessed how characteristics of fire regimes (frequency, time since fire, and burn severity) interacted with climate and invasive plants on measures of α-, β-, and γdiversities. Because β-diversity is a direct measure of community variability and reveals important Fire, Invasives, and Seed Banks in the Mojave 2 information about biodiversity loss, we further examined the nestedness and turnover components of β-diversity. Mean α and γ diversities were generally higher for burned locations than in unburned reference sites, however individual fire variables had little influence on patterns of seed bank diversity. Burned area seed banks tended to be dominated by non-native invasive species, primarily two grasses, (Bromus rubens, Bromus tectorum), as well as an invasive forb (Erodium cicutarium).The most striking pattern we observed was a collective sharp decline in α, β, and γ diversities with increased invasive species dominance, indicating the homogenization of seed bank communities with the colonization of invasive species after fire. Evidence of homogenization was further supported by reduced turnover and increased nestedness in burn areas compared to reference areas indicating potential biodiversity loss.